IMPLEMENTASI KEBIJAKAN APLIKASI PAYMENT ONLINE SYSTEM PAJAK BUMI DAN BANGUNAN (POS PBB-P2) DI KECAMATAN PANCA RIJANG - Arwang, Arwang; Muhammad Nur; Razak, Muhammad Rais Rahmat; Mustapa, Rasdiana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This stuy aims to analyze the implementation of the POS PBB-P2 application policy and to identify the factors influencing system adoption among taxpayers (WP) in Panca Rijang District, Sidenreng Rappang Regency. The research location was selected based on a persistent gap: despite the adoption of a digital system, tax revenue realization has consistently fallen below target over the past three years. This study employs a descriptive qualitative approach. Data were collected through interviews, observations, and document analysis. The findings reveal variations in implementation effectiveness. Internal aspects such as Communication, Disposition, and Bureaucratic Structure functioned strongly, marked by a high level of commitment among administrative staff. However, these internal strengths were undermined by external and material constraints that led to revenue stagnation: (1) limited communication and socialization efforts toward the public, and (2) inadequate material resources, including insufficient computer units, slow internet connectivity, and unstable electricity supply. The main barriers to taxpayer adoption include low digital literacy among elderly groups, limited awareness due to weak socialization, and perceived service risks resulting from inadequate infrastructure at the Technical Implementation Unit (UPT). It is recommended that the local government intensify socialization efforts with an emphasis on education for vulnerable groups, prioritize budget allocation for physical infrastructure improvement, and review penalty tariff regulations to enhance their effectiveness.